On Noah's ark - Brett, Jan (New York : G. P. Putnam's Sons, 2003)
Noah's granddaughter helps him bring the animals onto the ark, calm them down, and get them to sleep.
Keywords: Noah (Biblical figure) -- Fiction; Noah's ark -- Fiction; Animals -- Fiction; Grandfathers -- Fiction